Rancang Bangun Sistem Scada (Supervisory Control And Data Acquisition) pada Instalasi Pengolahan Air Sungai Cihideung Institut Pertanian Bogor - Agus Eko Handoko; Erizal .; Yudi Chadirin (PERTETA, 2017)
Abstract SCADA is a combination of telemetry and data acquisition. SCADA proceeding by means of accumulating some information and return back to center controlling, it is also implementing every analysis and necessary control through PID control system as a control parameter to SCADA input data system in this research. In designing PID control system it is needed the arrangement of P, I and D parameter in order to acquire output signal system to particular input system which has adjusted to necessity. The research was implemented on Water Treatment Plant in Bogor Agricultural University at Cihideung's area region. The NTU score as a starting operational data is necessary as a bench mark in PAC dose application which is obtained from the samples of morning and afternoon raw water and dose proportion is 75% for 14kgs PAC mixed with 200 Litre water within 30 NTU as the maximal treatment. 75% dose application can be imposed for 7 hours PAC usage. The result of research indicated that the variety of percentages value in PAC dose application delivered the advantage in operating of clean water processing installation particularly for PAC needed. Design Of SCADA System SCADA indicated the outcome of unit data acquirement on certain period to determine the PAC necessity in operating Water Treatment Plant. Abstrak SCADA merupakan kombinasi telemetri dan akuisisi data. SCADA mengumpulkan informasi dan mentransfer kembali ke pusat kendali serta melaksanakan setiap analisis dan kontrol yang diperlukan, melalui sistem kontrol PID sebagai parameter kontrol terhadap sistem masukan data unit SCADA pada penelitian ini. Dalam perancangan sistem kontrol PID yang perlu dilakukan adalah mengatur parameter P, I atau D agar tanggapan sinyal keluaran sistem terhadap masukan tertentu sesuai yang diperlukan. Penelitian dilakukan di instalasi pengolahan air bersih Institut Pertanian Bogor pada wilayah sungai Cihideung. Data awal operasional menunjukan untuk memberikan dosis PAC digunakan data acuan nilai NTU yang dilakukan dengan pengambilan sampel air baku pada pagi dan sore hari dengan nilai pemberian dosis 75% untuk 14kg PAC yang dicampur air 200 liter untuk perlakuan maksimal nilai 30 NTU. Pemberian dosis 75% tersebut berlaku untuk pengunaan PAC selama 7 jam. Hasil penelitian menunjukan bahwa variasi dalam nilai persentase pengunaan dosis PAC memberikan keuntungan dalam operasional instalasi pengolahan air bersih terutama untuk kebutuhan PAC. Rancang bangun sistem SCADA memberikan hasil dalam memperoleh data pada satuan waktu tertentu untuk menentukan kebutuhan PAC pada operasional instalasi pengolahan air.